Short-Term Climatic Effect of Gyaring and Ngoring Lakes in the Yellow River Source Area, China - Yang, Xianyu; Wen, Jun; Huang, Anning; Lu, Yaqiong; Meng, Xianhong; Zhao, Yong; Wang, Yurun; Meng, Lixia (Frontiers in Earth Science, 2022)
Based on the field observation and WRF-CLM model, the effects of Gyaring and Ngoring lakes on the short-term climate over the Yellow River source area were studied through two experiments with and without the lakes. A backward water vapor transfer model was also employed to investigate the contribution of water vapor evapotranspiration from the typical plateau lakes and various surface types to local precipitation. The results show that without the lakes, the sensible heat over the lakes increased by 120% whereas the latent heat decreased by 58.5%, and the height of atmospheric boundary layer increased from 500 m to 1500-2000 m during daytime. The sum of sensible and latent heat in the lake area simulated with and without the presence of lakes is 185.8 W m-2 and 130.3 W m-2, respectively. The precipitation amount over the lake area increased significantly without considering the lakes effect, generally by more than 20-40 mm. About 63.8% of total precipitation in Gyaring and Ngoring lakes was contributed by the external water vapor sources. The evapotranspiration from grassland was the secondary water vapor source for the precipitation in the study area and 25.2% of total precipitation was contributed by this source. Around 4.2% of total precipitation in the lake area was contributed by the evaporation from Gyaring and Ngoring lakes.